2017
DOI: 10.1044/2017_jslhr-l-17-0085
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Verb Learning: Preverbal and Postverbal Infants' Learning of Word–Action Relations

Abstract: https://doi.org/10.23641/asha.5592637.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Although these experimental studies provide insights into bilingual versus monolingual infants’ phonetic perception, lexical mapping and noun learning after first word onset, none compare bilinguals’ versus monolinguals’ emerging verb-action mapping prior to and after the transition to first words (see review, DeAnda, Poulin-Dubois, Zesiger & Friend, 2016). During lexical mapping development, a precursor to lexical comprehension, recent evidence suggests that monolingual postverbal infants (referring in that study to post verb comprehension onset) of 12- to 14 months tune into language-specific lexical properties, such as the greater frequency of nouns relative to verbs in their noun-friendly language ( noun bias , e.g., English; Gogate & Maganti, 2017). As these infants naturally learned more words, in particular, nouns in the noun-friendly language (e.g., English) as per maternal report on the MacArthur-Bates Communicative Development Inventories (MCDI, Fenson, Dale, Reznick, Bates, Thal & Pethick, 1994), their verb-action mapping in the laboratory was attenuated relative to infants who had not learned as many nouns.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although these experimental studies provide insights into bilingual versus monolingual infants’ phonetic perception, lexical mapping and noun learning after first word onset, none compare bilinguals’ versus monolinguals’ emerging verb-action mapping prior to and after the transition to first words (see review, DeAnda, Poulin-Dubois, Zesiger & Friend, 2016). During lexical mapping development, a precursor to lexical comprehension, recent evidence suggests that monolingual postverbal infants (referring in that study to post verb comprehension onset) of 12- to 14 months tune into language-specific lexical properties, such as the greater frequency of nouns relative to verbs in their noun-friendly language ( noun bias , e.g., English; Gogate & Maganti, 2017). As these infants naturally learned more words, in particular, nouns in the noun-friendly language (e.g., English) as per maternal report on the MacArthur-Bates Communicative Development Inventories (MCDI, Fenson, Dale, Reznick, Bates, Thal & Pethick, 1994), their verb-action mapping in the laboratory was attenuated relative to infants who had not learned as many nouns.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, tuning into a noun bias and learning more novel noun-object relations results in a temporary perceptual-lexical narrowing to nouns which, in turn, temporarily attenuates word-action mapping in postverbal relative to preverbal infants: the perceptual-lexical narrowing hypothesis (Gogate & Hollich, 2016; Gogate & Maganti, 2017). Substantiating this hypothesis, the postverbal 12- to 14-month-old infants failed to learn two novel word-action mappings when exposed to the pairings during habituation, whereas the preverbal 8- to 9-month-old infants succeeded in learning these mappings (Gogate & Maganti, 2017). Early heightened perception of word-action relations likely emerges from young infants’ perception of their own and others’ actions (e.g., 2 months; Bahrick & Watson, 1985) that far surpasses their object and face perception when pitted against one another (e.g., 5.5 months; Bahrick, Gogate & Ruiz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Far from being an isolated modality only relevant for language learning, though, emerging evidence suggests that linguistic modulations, like enhanced social‐emotional and eye gaze cues, co‐occur with motion modulations (Nagai & Rohlfing, ; Rohlfing et al, ; )and together optimize action learning conditions (Brand & Tapscott, ; ). Complementarily, extensive evidence exists for the opposite effect, namely that motions of parents and infants can facilitate language learning (Chang, de Barbaro, & Deák, ; Gogate, Bolzani, & Betancourt, ; Gogate & Maganti, ; Gogate, Maganti, & Laing, ; Matatyaho & Gogate, ; Matatyaho‐Bullaro et al, ; Nomikou, Koke, & Rohlfing, ; Rader & Zukow‐Goldring, ; Yoshida & Burling, ). Consequently, for the teaching potential of parental modulations to be fully understood, future research must consider the entire repertoire of infant‐directed behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we used fixed‐time trials during the habituation phase in order to make the experiment analogous to past studies using a minimal consonantal contrast (e.g., Fennell & Waxman, ; Werker et al., ). However, some recent studies also employ infant‐controlled trials (e.g., see Gogate & Maganti, ; Hay et al., ; Singh et al., , ) in which the trial terminates if infants look away from the display for a certain amount of time (usually 1 or 2 sec). Although we are not aware of any studies which directly suggest that fixed‐time trials and infant‐controlled trials in the habituation phase yield different looking behaviors in the test phase (but see Gogate & Maganti, for a detailed review of the dynamics of infant attention shift), it is possible that this methodological difference may contribute to the result we obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Infants start to learn word and referent associations as early as 6–8 months (e.g., Tincoff & Jusczyk, ) and produce words by the end of their first year. A wide range of studies has suggested that word‐referent learning is influenced by multiple factors such as the learner's current level of vocabulary development (Werker, Fennell, Corcoran, & Stager, ) and language background (Burnham et al., ; Fennell, Byers‐Heinlein, & Werker, ; Singh, ; Singh et al., , ), the familiarity of the word being learned (Fennell & Werker, ), and the presence or absence of synchrony between word presentation and object motion during the task (Gogate, ; see also Gogate & Maganti, ; He & Lidz, for verb‐action learning). Phonetic properties are also known to be influential in word‐referent, especially word–object, learning.…”
mentioning
confidence: 99%